(untitled)
This paper attempts to describe and explains the phonological process of vowel harmony in two indigenous languages of Sabah, namely Dusun Kimaragang and Rungus. In terms of language classification, these two languages belong to the Dusunic language family. In order to explain the process of vowel harmony that operates here, the present study adopts the theoretical framework of autosegmental phonology. This study observes that the harmony rule that applies in Dusun Kimaragang and Rung us demonstrates some forms of similarities and differences. In both languages, the harmony rule involves a mapping of ± low feature that spreads from right to left, that is from the root vowel to the prefix vowel. The spreading process can pass through two consecutive vowels. A major distinction that distinguishes the two languages is that in Rung us the spreading of the ±low] feature of the root vowel can run through a high vowel Iii of the prefix, where as in Dusun Kimaragang such spreading is inapplicable. This distinction can be accounted for by assuming that the high vowel /i/ in Dusun Kimaragang is specified with a feature -low in its lexical representation, where as such representation does not occur in Rungus. This feature will block the spreading of +low] feature to the preceding vowel because the mapping will result a crossing of autosegmental lines. On the contrary, without that feature, the spreading process will apply accordingly. The present analysis explain the process of vowel harmony in both languages successfully and adequately. , number=4, journal=Jurnal Bahasa, year=2003, month=Dec., pages=607–623